2021
DOI: 10.3389/fphys.2021.684529
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and Tensin Homolog in Non-neoplastic Digestive Disease: More Than Just Tumor Suppressor

Abstract: The Phosphatase and tensin homolog (PTEN) gene is one of the most important tumor suppressor genes, which acts through its unique protein phosphatase and lipid phosphatase activity. PTEN protein is widely distributed and exhibits complex biological functions and regulatory modes. It is involved in the regulation of cell morphology, proliferation, differentiation, adhesion, and migration through a variety of signaling pathways. The role of PTEN in malignant tumors of the digestive system is well documented. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 157 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…Additionally, two independent studies that utilized the prostate cancer model in MKK7 knockout mice with MKK4 and Phosphatase and tensin homolog (PTEN) deficiency showed rapid development of invasive adenocarcinoma ( Hubner et al, 2012 ; Atala 2013 ). PTEN is a phosphatase family member ( He et al, 2021 ). Mutations of this phosphatase gene are known in the development of many cancers, including prostate cancer ( Li et al, 1997 ; He et al, 2021 ).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, two independent studies that utilized the prostate cancer model in MKK7 knockout mice with MKK4 and Phosphatase and tensin homolog (PTEN) deficiency showed rapid development of invasive adenocarcinoma ( Hubner et al, 2012 ; Atala 2013 ). PTEN is a phosphatase family member ( He et al, 2021 ). Mutations of this phosphatase gene are known in the development of many cancers, including prostate cancer ( Li et al, 1997 ; He et al, 2021 ).…”
Section: Cancermentioning
confidence: 99%
“…PTEN is a phosphatase family member ( He et al, 2021 ). Mutations of this phosphatase gene are known in the development of many cancers, including prostate cancer ( Li et al, 1997 ; He et al, 2021 ). On the other hand, MKK4, a kinase that works oppositive to phosphatases, has been found to have a loss of function mutation in 5% of human cancer ( Whitmarsh and Davis 2007 ) ( Table 1 ).…”
Section: Cancermentioning
confidence: 99%
“…PTEN inhibits the PI3K-Akt and mammalian target of rapamycin (mTOR) signaling pathways. 5 Reduced PTEN activity causes increased phosphorylation of various cell proteins, affecting processes of cell growth, migration, and death. 6 Overactivation of the PI3K/AKT/mTOR pathway can result in the formation of benign and malignant tumors and overgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a tumor suppressor gene that exerts vital effects on cell growth, proliferation, migration, signal transmission, invasion, and apoptosis [ 14 ]. Existing studies have also demonstrated that abnormal PTEN expression is associated with non-neoplastic disease [ 15 ]. Activation of pro-fibrotic signaling pathways through PTEN may lead to fibrosis in the liver, lung, and kidney tissues [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%